Relation between thermal effect and phase transformation of aluminium matrix surface composite adding Al-based amorphous fabricated by FSP. (September 2016) - Liu, Peng; Li, Yang; Zhang, Ge-ming; Feng, Ke-yun
Abstract: Thermal analysis and phase transformation of aluminium matrix surface composite adding Al-based amorphous fabricated by FSP was studied. The test result indicated that the surface composite mainly is composed of a large number of nano structures. AlCuMg precipitated phases and incomplete crystallization amorphous phases form the in a nano-structure matrix. The exothermic area of base metal is bigger than the one of the surface composites. The incomplete crystallization amorphous materials could experience the liquification and endothermic process: Al84.2 Ni10 La2.1  → fcc-Al + NiAl3  + La3 Al11 . Moreover, the thermal stability of the surface composites is higher than that of the base metal. Highlights: Thermal-analysis (DSC) of Al-based surface composite was used and studied. Relation between thermal-analysis and phase transformation was studied. The liquification and endothermic process of the incomplete crystallization amorphous materials were discussed.